Cultural biology of the blue mussel, Mytilus edulis (Linnaeus, 1758) in inland saline water in Western Australia - Dinh, Quang Huy (Curtin University, 2016)
This research investigated the technical feasibility of culturing the blue mussel Mytilus edulis in potassium fortified inland saline water. The results showed that the blue mussels in 100% K+ fortified inland saline water can be successfully cultured. One hundred fortification of inland saline water also improves the settlement rate of mussel larvae and reduces the deformities during early larval life. The mussels are isosmotic at 27 ppt in inland saline water.